2017
DOI: 10.24843/jhsm.2017.v01.i01.p07
|View full text |Cite
|
Sign up to set email alerts
|

Screening Potential Antioxidant and Antibacterial Activities of Protein Hydrolysates Derived From Germinated Lablab Bean, Pigeon Pea and Kidney Bean

Abstract: Protein hydrolysate contains a mixture of various lengths of short peptides chain and free amino acids that may excert biological activities. This research aims to screen potential antioxidant and antibacterial activities of protein hydrolysate produced from three kinds of germinated beans i.e. lablab bean (Lablab purpureus), pigeon pea (Cajanus cajan (L.) Millsp) and kidney bean (Phaseolus vulgaris) through enzymatic hydrolysis process. The steps of research included germination process of&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This was followed by other formulations, which had varying levels of pigeon pea. Pigeon pea hydrolysates have been reported to demonstrate antioxidant activities 38 . The presence of saturated double bonds and benzene rings joined by a planar unsaturated C2 structure in the structure of bioactive compounds enhances this antioxidant effect 39 .…”
Section: Antioxidant Activity Of Mixtures Of Hydrolysed Germinated So...mentioning
confidence: 99%
“…This was followed by other formulations, which had varying levels of pigeon pea. Pigeon pea hydrolysates have been reported to demonstrate antioxidant activities 38 . The presence of saturated double bonds and benzene rings joined by a planar unsaturated C2 structure in the structure of bioactive compounds enhances this antioxidant effect 39 .…”
Section: Antioxidant Activity Of Mixtures Of Hydrolysed Germinated So...mentioning
confidence: 99%
“…The noodle with thymol was unacceptable for consumers with the a barrier against numerous antibiotic molecules and the enzymes of the periplasmic spaces. Ratnayani et al (2017) indicated that protein hydrolysates from beans had no antimicrobial effects on E. coli and S. aureus. This is because protein hydrolysates are mixtures of different types of amino acids and are of different sizes.…”
Section: Sensory Properties Of Cooked Noodlesmentioning
confidence: 99%